Infections in patients admitted with decompensated chronic liver disease in a tertiary level hospital - Subedi, Prashant; Peeyush, Denis; Mandal, Rajesh Kumar; Sapkota, Prakash; Pradhan, Bickram (Journal of Advances in Internal Medicine, 2025)
INTRODUCTION Infection is one of the major complications leading to hospital admission and mortality in patients with decompensated chronic liver disease (CLD). This study aims to determine the clinical profile and outcome of these patients which is very limited in our part of the world. METHODS In this prospective observational study; we included all 184 patients from January 2025 to April 2025 with decompensated CLD admitted in Gastroenterology and Hepatology ward of B.P. Koirala Institute of Health Sciences. The clinical profile and outcomes of these patients were evaluated and analyzed. Common scores used in patients with cirrhosis including CTP (Child-Turcotte Pugh), MELD-Na (Model for end-stage liver disease) and SOFA (Sequential organ failure assessment) score were evaluated for their role in predicting mortality. RESULTS The prevalence of infection in CLD was found to be 37.5% with male predominance of 53.8%; mean age was 51.42 years (SD: 11.85). Alcohol related cirrhosis was the commonest etiology and other etiology included autoimmune hepatitis, chronic HCV, chronic HBV, Wilson’s disease, metabolic syndrome associated steatotic liver disease (MASLD), PSC related and cryptogenic. Spontaneous bacterial peritonitis was the most common infection with 26 (37.7%) followed by urinary tract infection, pneumonia and skin and soft tissue infection. Infection was significantly associated with longer hospital stay, higher MELD-Na, CTP and SOFA scores of patients. Area under the curve for MELD-Na had the highest discriminative ability to predict mortality with cut-off values of 22.5 with sensitivity of 93.75% and specificity of 62.26%. The in-hospital mortality in patients with decompensated CLD with infection was 23.2%. CONCLUSION Infection in decompensated CLD patients is a major predictor of adverse outcomes including mortality. Early identification and aggressive management of infection in this group of patients is needed to prevent adverse outcomes.